2001
DOI: 10.1038/sj.bjp.0704396
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effect of synthetic somatostatin analogues in the rat

Abstract: u.9., Hungary 1 Somatostatin (6.11 nmol kg 71 i.p.) inhibited neurogenic plasma extravasation evoked by 1% mustard oil and non-neurogenic oedema induced by 5% dextran in the rat skin. 2 Cyclic synthetic octapeptide (TT-248 and TT-250) and heptapeptide (TT-232) somatostatin analogues proved to be more e ective in reducing neurogenic and non-neurogenic in¯ammatory reactions but octreotide had no in¯uence on either neurogenic or non-neurogenic in¯ammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 35 publications
5
61
0
2
Order By: Relevance
“…The amount of the accumulated Evans blue was expressed as mg of dye/g of wet tissue. 27) Isolation of Rat Neutrophils Blood was collected in heparinized tubes. A 6% dextran solution was added to the blood and the supernatant was collected after 1 h. The equal parts of Lymphoprep TM and the supernatant were mixed.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of the accumulated Evans blue was expressed as mg of dye/g of wet tissue. 27) Isolation of Rat Neutrophils Blood was collected in heparinized tubes. A 6% dextran solution was added to the blood and the supernatant was collected after 1 h. The equal parts of Lymphoprep TM and the supernatant were mixed.…”
Section: Methodsmentioning
confidence: 99%
“…Direct evidence for the involvement of somatostatin of neural origin in the observed antiinflammatory and analgesic actions was also provided (1-3, 8, 9). Results obtained with synthetic somatostatin receptor agonists suggested that these inhibitory effects were mediated by receptors of the SRIF 2 family (sst 4 /sst 1 ) (8,11,15,16,(19)(20)(21)25). However, because of the lack of sst 4 -selective antagonists, the precise receptor mechanisms of the somatostatin-mediated ''sensocrine'' inhibitory actions on inflammation and nociception have remained to be elucidated until the generation of sst 4 receptor gene-deficient mice.…”
Section: Figmentioning
confidence: 99%
“…4). Several data indicate that receptors in the SRIF 1 group mediate the endocrine and antiproliferative effects, whereas the SRIF 2 group, predominantly the sst 4 receptor, is responsible for the anti-inflammatory and antinociceptive actions (3,15,16).…”
mentioning
confidence: 99%
“…throughout the experimental period of 18 days dose-dependently inhibits oedema and inflammatory mechanical hyperalgesia (Pinter et al 2002). Octreotide had also no such effect in mustard oil-induced neurogenic inflammatory models, where TT-232 was proved to be highly effective (Helyes et al 2001). Therefore, we presume that SSTR4 -and less importantly also SSTR1 -mediated signalling is responsible for the anti-inflammatory action of somatostatin and TT-232.…”
Section: Sstr4 and Sstr1 Play An Important Role In The In Vivo Anti-imentioning
confidence: 83%